Sosialisasi dan Pelatihan “Pemanfaatan Limbah Plastik Menjadi Barang yang Bernilai Ekonomis” di Desa Kulim Jaya Kecamatan Kempas Kabupaten Indragiri Hilir - Heltina, Desi; Fadhil, Rayhan; Iwana, Iwana; Fahreza, Muhammad; Efrina, Restika (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
People consider inorganic waste to be useless even though it can be turned into beautiful crafts. Examples of crafts from inorganic waste are pencil cases, flowers, key chains, vases and so on. The activities carried out by UNRI KKN students aim to convert inorganic waste into useful and economically valuable goods. This activity was carried out at village Kulim Jaya Kempas Subdistrict,Indragiri Hilir using the Learning by Doing approach. UNRI KKN students learn by practicing directly how to process inorganic waste into flower crafts from straws using prepared tools and materials. This approach is more effective in achieving outcomes in KKN activities in Kulim jaya. The result of implementing this Integrated Real Work Lecture (KKN) activity is to provide information and innovation about managing inorganic waste into crafts so that students are able to process inorganic waste into creative crafts. This activity can also be an option to reduce waste, especially inorganic waste. Most trash comes from people living in towns and cities; most of it is biodegradable (around 75 percent) and the remainder is inorganic. Briquettes, compost, and biogas are just a few of the many products that have benefited from organic waste's widespread use. However, only a small percentage of garbage is being recycled into compost or compostable materials. Meanwhile, inorganic waste is very difficult to recycle and cannoteven be recycled naturally, so it requires a very large area of land to offset the production of this waste. Garbage is one of the problems of human life. When people's perspectives of waste, which once saw waste as worthless waste, are changed into crafts that have uses and economic value, those people's perceptions of waste shift, too.